Architecture of HAP-anammox granules contributed to high capacity and robustness of nitrogen removal under 7°C. (1st November 2021) - Song, Ying; Lin, Lan; Ni, Jialing; Ma, Haiyuan; Qi, Wei-Kang; Li, Yu-You
Highlights: A nitrogen removal rate of 3.1 g-N/L/d was obtained at 7°C for long-term operation. Temperature dependence of cold cultured Ca. Kuenenia was elucidated. Hierarchical architecture of HAP-anammox granules was characterized as three layers. Peeling behavior of HAP-anammox granules under low temperatures was illustrated. Abstract: The anaerobic ammonium oxidation (anammox) process is an autotrophic nitrogen removal process with great potential as a cost-effective and highly efficient technology in the wastewater treatment field. The main challenges yet to be overcome in this new frontier technology are operating at lower temperatures and achieving a high and stable nitrogen removal efficiency. In this study, an up-flow expanded bed reactor with hydroxyapatite (HAP)-anammox granules was operated for more than 200 days at 7°C. The nitrogen loading rate (NLR) was improved from 1.0 g-N/L/d to 3.6 g-N/L/d, together with a high-level nitrogen removal efficiency of 84-92%, which is the highest to date at extremely low temperatures in a continuous experiment. Candidatus Kuenenia was revealed to be the only dominant anammox genus, with a relative abundance of 35.3-37.5%. The optimal operational temperature was around 35°C and the apparent activation energy (Ea ) was calculated as 78.37 kJ/mol. The three-layers architecture and architectural evolution of HAP-anammox granules into HAP-cores and peeling biofilms with outstanding settling performance were characterized. Under 7 °C, the high capacity of nitrogen removal with robust removal efficiency using HAP-anammox granules was achieved. Graphical Abstact: Image, graphical abstract